RESPON VARIETAS PADI TAHAN SALIN TERHADAP BEBERAPA DURASI GENANGAN DENGAN TINGKAT SALINITAS BERBEDA - Erick Firmansyah; Budiastuti Kurniasih; Didik Indradewa (Program Studi Agroteknologi INSTIPER, 2017)
Indonesia population predicted to reach 304.9 million in 2035 and requires 70% more rice as food supply than today. The fulfillment of food supply experienced constraints such as submergence and salinity caused by climate change. Salinity and submergence stresses may occur in the same time, and the crop response to them has not been widely known. Research has been done to find out the responses of rice to salinity and submergence. The submergence level as the first factor consists of three levels (without submergence (R0); one-week submergence (R1); And two-week submergence (R2), salinity level as a second factor consists of two levels non saline (S1); And saline (S2) to obtain six combinations and each combination is repeated three times. Observations were made on the ratio of the leaf area ratio, the typical leaf area, the canopy -root ratio, the typical leaf weight and the canopy growth rate of the canopy. The weight of grain per clump becomes the observed production parameter at the end of the generative phase. The results showed that there was interaction between submergence duration and salinity level on leaf area ratio, typical leaf area, and canopy-root ratio. Observation of typical leaf weight and relative growth rate showed the treatment of submergence and salinity gave an individual effect. Two weeks of submergence cause plant to death. The saline treatment in all submergence levels resulted in a decrease in the weight of grain per hill. Plants survived one-week non-saline submergence, but two weeks non-saline submergence caused the plant to di",